Swiss students and young physicians want a flexible goal-oriented GP training curriculum. (3rd July 2018) - Rozsnyai, Zsofia; Tal, Kali; Bachofner, Marius; Maisonneuve, Hubert; Moser-Bucher, Cora; Mueller, Yolanda; Scherz, Nathalie; Martin, Sebastien; Streit, Sven
Abstract: Background: A growing shortage of general practitioners (GPs), in Switzerland and around the world, has forced countries to find new ways to attract young physicians to the specialty. In 2017, Switzerland began to fund hundreds of new study places for medical students. This wave of young physicians will soon finish University and be ready for postgraduate training. We hypothesized that an attractive postgraduate training program would encourage interested young physicians to pursue a GP career. Methods: This is a cross-sectional survey of young physicians from the Swiss Young General Practitioners Association (JHaS), members of Cursus Romand de médecine de famille (CRMF), and all current medical students (5 th or 6 th years) (n = 554) in Switzerland, excluding students indicating definitely not to become GPs. We asked all if they were likely to become a GP (Likert: 1-10), and then asked them to score general features of a GP training curriculum, and likely effects of the curriculum on their career choice (Likert scale). They then rated our model curriculum (GO-GP) for attractiveness and effect (Likert Scales, open questions). Results: Most participants thought they would become GPs (Likert: 8 of 10). Over 90% identified the same features as an important part of a curriculum ("yes" or "likely yes"): Our respondents thought the GO-GP curriculum was attractive (7.3 of 10). It was most attractive to those highly motivated to become GPs. After reviewing the curriculum, most respondents (58%) felt GO-GP would make them more likely to become a GP. Almost 80% of respondents thought an attractive postgraduate training program like GO-GP could motivate more young physicians to become GPs. Conclusions: Overall, medical students and young physicians found similar features attractive in the general and GO-GP curriculum, regardless of region or gender, and thought an attractive curriculum would attract more young doctors to the GP specialty. Key points: An attractive postgraduate training program in general practice can attract more young physicians to become GPs. In this study cross-sectional survey including medical students (n = 242) and young physicians (n = 312) we presented general features for a curriculum and a model curriculum for general practice training, for evaluation of attractiveness to our study population. General practice training curriculum provides flexibility in choice of rotations, access to short rotations in a wide variety of medical specialties, training in specialty practices as well, mentoring and career guidance by GPs and guidance in choosing courses/certificate programs necessary for general practice. These findings help building attractive postgraduate training programs in general practice and fight GP shortage.